Search for a new bottomonium state decaying to Upsilon(1S)pi(+)pi(-) in pp collisions at root s=8 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; Ghete, V; et al. (Elsevier, 2013)
The results of a search for the bottomonium counterpart, denoted as Xb, of the exotic charmonium state X(3872) is presented. The analysis is based on a sample of pp collisions at s=8 TeV collected by the CMS experiment at the LHC, corresponding to an integrated luminosity of 20.7 fb-1. The search looks for the exclusive decay channel Xb→Υ{hooked}(1S)π+π- followed by Υ{hooked}(1S)→μ+μ-. No evidence for an Xb signal is observed. Upper limits are set at the 95% confidence level on the ratio of the inclusive production cross sections times the branching fractions to Υ{hooked}(1S)π+π- of the Xb and the Υ{hooked}(2S). The upper limits on the ratio are in the range 0.9-5.4% for Xb masses between 10 and 11 GeV. These are the first upper limits on the production of a possible Xb at a hadron collider. © 2013 CERN.